Identification of Ecological Functional Areas and Scenario Simulation Analysis of the Wanjiang Urban Belt from a Trade-Off/Synergy Perspective - Yuchun Wang; Yufeng Ang; Yingying Zhang; Yunfeng Ruan; Bingyi Wang (Land)
Identifying ecological functional areas by clarifying the trade-off synergies of multiple ecosystem services to meet the practical needs of coordinating different ecosystem services in a specific region is highly important. Based on InVEST, RUSLE and other models, this study analyzed the tradeoff synergies of five typical ecosystem services in the Wanjiang Urban Belt from 1990 to 2020 using Pearson correlation analysis, and self-organizing map (SOM) carried out ecological functional zoning. The PLUS model was used to simulate the evolution of ecological functional zones in 2030. The results revealed that (1) from 1990 to 2020, water yield (WY), soil reservation (SR), and food production (FP) services in Wanjiang Urban Belt increased, whereas carbon storage (CS) and habitat quality (HQ) services decreased. The value of ecosystem services showed a pattern of “high in the south and low in the north”. (2) WY–SR, WY–HQ, HQ–CS, and HQ–SR were synergistic, and the synergistic relationship showed a weakening trend. There were trade-offs in WY–CS, WY–FP, and SR–FP, and the trade-off effects increased with time. (3) The study area was divided into an ecological transition area, an ecological conservation area, an urban development area, an ecological restoration area, an agroecological area, and a water conservation area, and the functions and structures of each cluster significantly differed. (4) Under the natural development scenario, the scales of the ecological transition, ecological conservation, and agroecological areas increased. Under the cropland protection scenario, the urban development and ecological conservation areas began to transform into agroecological areas. Under the urban development scenario, the transfer of areas from ecological conservation, ecological restoration, and agroecological areas to urban development areas increased. In conclusion, the ecosystem services of the Wanjiang Urban Belt are dominated by synergistic effects, but there is a potential risk of shifting to trade-off relationships. In the future, targeted regional ecosystem optimization measures according to the evolution status of each ecological functional zone are urgently needed to provide references for territorial space management and control in this region.